Clinical evaluation of a matrix metalloproteinase-12 cleaved fragment of titin as a cardiovascular serological biomarker - Vassiliadis Efstathios (Journal of Translational Medicine, 2012)
Abstract Background Titin is a muscle-specific protein found in cardiac and skeletal muscles which is responsible for restoring passive tension. Levels and functioning of titin have been shown to be affected by cardiac damage. Due to the inherent difficulty of measuring titin levels in vivo in a clinical setting, we aimed to develop an assay that could reliably measure fragments of degraded titin in serum and potentially be used in the assessment of cardiac muscle damage. Methods A competitive ELISA was developed to specifically measure levels of the titin sequence 12670’ NVTVEARLIK 12679’, derived by the degradation of titin by matrix metalloproteinase (MMP)-12. Serum samples from 90 individuals were divided into 3 equally sized groups. One group had been diagnosed with acute myocardial infarction (AMI) while the remaining two were asymptomatic individuals either with CT-scan signs of coronary calcium (CT-plusCa) or without coronary calcium (CT-noCa). Results Mean geometric levels of the titin fragment in the CT-noCa group were 506.5 ng/ml (±43.88). The CT-plusCa group showed 50.6% higher levels of the marker [763 ng/ml (±90.14)] (P < 0.05). AMI patients showed 56.3% higher levels [792 ng/ml (±149)] (P < 0.05). Conclusions The titin-12670 fragment is present in both individuals with undiagnosed and diagnosed CVD. The statistically significant increase in level of the marker in the AMI group is indicative that this neoepitope biomarker may be a useful serological marker in AMI.